Dissolution studies of generic medications: New evidence of deviations from the transitivity principle - Ruiz, María Esperanza (2012)
Current international criteria to guarantee that two equivalent pharmaceutical medications are interchangeable establish that substitution may be done whenever studies indicate that a generic or similar product is bioequivalent to the reference product. The principle of transitivity defines interchangeability between approved pharmaceutical equivalents (i.e., given two generic products B and C and a reference A, if B and C are bioequivalent to A, then B and C are assumed to be bioequivalent although bioequivalence between them has not been actually assessed). In this study, the goal was to test the applicability of the transitivity principle in establishing interchangeability between pharmaceutical equivalents. We obtained the dissolution profiles of all the products corresponding to tablets of ranitidine 300 mg and cephalexin 500 mg (Biopharmaceutics Classification System Class III), furosemide 40 mg (Class IV), and ibuprofen 400 mg and 600 mg (BCS Class II) available in the Argentinean pharmaceutical market. Dissolution profiles of all possible pairs were compared through similarity factor f2. The results obtained bring into question the general validity of the transitivity principle, as many examples were observed to have dissolution profiles similar to the reference product, yet were not equivalent. Although this has only been assessed through in vitro tests, our results are potentially important, as a number of recent reports have suggested the extension of biowaivers to certain BCS Class II and Class III products, including ranitidine hydrochloride and ibuprofen.